Deskripsi Pengetahuan Tentang Manajemen Nyeri Pada Lansia - Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2019)
The percentage of elderly people in Indonesia increases every year to reach 9.27 percent or around 24.49 million people in 2018. The health problem that often occurs in the elderly is chronic pain due to several diseases. Pain is a general picture that persists and is closely related to substantial morbidity in the elderly. This study aims to get an overview of elderly knowledge regarding pain management. Using a quantitative research design and analytical description approach, this study was conducted on 46 elderly people in the working area of the Guguak Panjang Health Center, Bukittinggi City. The elderly were given a questionnaire based on the Nursing Outcome Classification regarding Knowledge: Pain management. Data analysis used descriptive analysis to see the description of each statement point in the questionnaire. The results of this study indicate that there are still 43.5% of the elderly lacking in poor knowledge in pain management. Less knowledge influences how to deal with pain in the elderly. It is expected that the elderly will be given education about pain management so that they can improve their health status.Keywords : Pain, Elderly, Knowledge